Phytogenetic resources in the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The International Board for Plant Genetic Resources (IBPGR) has been involved since 1984 in the preparation of an inventory of such resources in the Sahel in collaboration with national institutes in the ten countries concerned. The first objective...